DETERMINANTS OF LOW BACK PAIN PREVENTION BEHAVIOR OF TOFU INDUSTRY WORKERS - Sugiarto; Parman; Rara Marisadayana (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Low Back Pain (LBP) is a common occupational health problem among workers, especially in formal industries such as the tofu industry; to prevent serious health impacts, it is necessary to apply appropriate ergonomic behavior. Purpose: This research aims to determine ergonomic behavior in the prevention of LBP in tofu industry workers. Method: This research used a cross-sectional design. The research was conducted in the tofu industry in Jambi City from May to June 2024. A total of 88 tofu industry workers were selected using purposive sampling. Data were collected through interviews using a structured questionnaire. Bivariate and multivariate analyses were performed to identify factors associated with ergonomic behavior. Result: The finding showed that 47.7% of respondents had poor behavior, 50.0% of respondents had poor knowledge, 26.1% of respondents had poor attitudes, 19.3% of respondents had inadequate experience, and 33.0% of respondents had poor perceptions regarding ergonomics. The results of bivariate analysis found that ergonomic behavior was related to knowledge (p-value = 0.019), experience (p-value = 0.001), and perception (p-value = 0.034). No significant association was found between attitude and ergonomic behavior (p-value = 0.800). Multivariate analysis indicated that workers with inadequate experience were approximately seven times more likely to exhibit poor ergonomic behavior after controlling for knowledge and perception (PR = 7.703; 95% CI: 1.537 – 39.619; p = 0.013). Experience was identified as the most dominant factor influencing ergonomic behavior. Conclusion: Ergonomic behavior is significantly associated with knowledge, experience, and perception. The most dominant factor in ergonomic behavior is experience after controlling for knowledge and perception.